Application of Knowledge Sharing at UPT Puskesmas Desa Medan Krio - Abdi Mubarak Syam (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Objective: This review aims to find a relationship between the increasing number of monkeypox cases, especially in LGBT community, based on the literature study approach and case reports. One of the non-medicamentous ways is to reduce travelling abroad, especially in countries with many monkeypox cases. Preventing direct contact, such as abstaining from sex and using condoms, is also a way to reduce the morbidity of monkeypox infection, especially in LGBT community. The treatment has not proven effective, and the available vaccines, especially in Indonesia, are still limited. Only a few cases in Indonesia have been reported. Method: This research is based on a literature study approach and case reports with article sources obtained from Eurosurveillance and Elsevier. It restricts articles using the keywords